2015
DOI: 10.1186/s12906-015-0747-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Piper laetispicum extract (EAE-P) during chronic unpredictable mild stress based on interrelationship of inflammatory cytokines, apoptosis cytokines and neurotrophin in the hippocampus

Abstract: BackgroudThe Piper laetispicum C.DC. (Piperaceae) is a traditionally used herb in China for invigorating circulation and reducing stasis, detumescence and analgesia, which is distributed in the southern part of China and the southeastern part of Asia. Previous studies demonstrated that the ethyl acetate extract (EAE-P) of P. laetispicum possesses a significant antidepressant-like effect at doses higher than 60 mg/kg in Kunming (KM) mice, and this effect was not due to an increase in locomotive activity.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…In particular, in line with the literature and our hypothesis, treatment in a stressful condition overall led to an anti-inflammatory response (Cheng et al, 2016;Ji et al, 2014;Jiang et al, 2013;Lu et al, 2014;Tianzhu et al, 2014;Wilson et al, 2014;Xie et al, 2015). By contrast, fluoxetine treatment in an enriched condition led to an increased expression of inflammatory genes.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, in line with the literature and our hypothesis, treatment in a stressful condition overall led to an anti-inflammatory response (Cheng et al, 2016;Ji et al, 2014;Jiang et al, 2013;Lu et al, 2014;Tianzhu et al, 2014;Wilson et al, 2014;Xie et al, 2015). By contrast, fluoxetine treatment in an enriched condition led to an increased expression of inflammatory genes.…”
Section: Resultssupporting
confidence: 91%
“…These findings indicate that fluoxetine increases the overall inflammatory milieu in the enriched condition, while exerting an opposite effect in the stressful condition. The latter result is in line with previous studies showing that fluoxetine, when administered to mice exposed to a stressful environment, overall reduces hippocampal expression of pro-inflammatory cytokines (Cheng et al, 2016;Ji et al, 2014;Jiang et al, 2013;Lu et al, 2014;Tianzhu et al, 2014;Wilson et al, 2014;Xie et al, 2015).…”
Section: Fluoxetine Affects Hippocampal Inflammatory Mediatorssupporting
confidence: 92%
“…Each of these models entails different mechanisms, such as changes in kynurenine metabolites, altered neurotransmitter signaling, and others [21, 36]. Additionally, some similarities such as alterations in cytokines and BDNF levels are also observed in most models, mimicking observations recorded in psychiatric patients [37, 39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory agents may be a useful antidepressant therapy or an adjuvant to the currently available conventional therapies (20). Mice exposed to CUMS significantly enhanced the productions of TNF-a and IL-6 in the hippocampus, and these changes could be reversed by treatment with antidepressant therapy (46). The results of our present study also demonstrated that CUMS treatment significantly enhanced the levels of TNF-a and IL-6 in the hippocampus and cerebral cortex of the mice, whereas treatment with IRN could restore the release of TNF-a and IL-6 induced by CUMS.…”
Section: Discussionmentioning
confidence: 99%